Analisis Pemasaran Produk Simpanan Dan Pembiayaan Pada BMT Insan Madani - Satriana, Desmi; Hartini, Dwi; Indah Lestari, Dwi; Mai Fransiska, Helga; Imanda, Rafly (Risalah Iqtishadiyah, 2024)
In BMT Insan Madani there are business fields, one of which consists of collecting funds and distributing funds, namely Savings and Financing. These savings products consist of savings products, such as (wadiah savings, education savings, hajj/umrah savings, holiday savings, and qurban savings), and then financing products, such as (murabahah, mudharabah, musyarakah, and IMBT). The purpose of this study is to determine the implementation of marketing savings and financing products. This study uses a qualitative method, namely by collecting data by conducting interviews. The results of this study are that BMT is present as a place to collect funds for people who need a place to store funds in the future, both for education, hajj/umrah, and even holidays. In addition, BMT is also a place to provide funds and acts as a capital manager for people who lack funds in building their businesses. The initial procedure carried out by BMT Insan Madani in marketing its products, they conduct a location survey, this is done to find information about the needs and problems that exist in the community, after the location survey is carried out, the BMT will collect funds or distribute funds with savings products and provisions available at BMT Insan Madani, according to the needs of the community.